Transcripts related with ammonium use and effects of gibberellin on expressions of the transcripts responding to ammonium in two invasive and native Xanthium species - Zhang, Chang; Luo, Jia-Jun; Zuo, Jing-Bo; Zhang, Zheng; Wang, Shi-Ting; Zhang, Xiao-Jia; Fu, Tian-Si; Feng, Yu-Long (Frontiers in Plant Science, 2022)
Soil nitrogen forms are important for exotic plant invasions. However, little effort has been made to study the molecular mechanisms underlying the utilization of different N forms in co-occurring invasive and native plants. The invasive plant Xanthium strumarium prefers nitrate relative to ammonium, and mainly invades nitrate-dominated environments, while it co-occurring native congener X. sibiricum prefers ammonium. Here, we addressed the genetic bases for the interspecific difference in ammonium use and the effects of gibberellin (GA). Twenty-six transcripts related with GA biosynthesis and ammonium utilization were induced by ammonium in X. sibiricum, while only ten in X. strumarium and none for ammonium uptake. XsiAMT1.1a, XsiGLN1.1 and XsiGLT1b may be crucial for the strong ability to absorb and assimilate ammonium in X. sibiricum. All tested transcripts were significantly up-regulated by GA1 and GA4 in X. sibiricum. XsiGA3OX1a, which was also induced by ammonium, may be involved in this regulation. Consistently, glutamine synthetase activity increased significantly with increasing ammonium-N / nitrate-N ratio for X. sibiricum, while decreased for X. strumarium. Our study is the first to determine the molecular mechanisms with which invasive and native plants use ammonium differently, contributing to understanding the invasion mechanisms of X. strumarium and its invasion habitat selection.